The behavioural ecology behind anti-predator mechanisms: diversity, ontogenetic changes and sexual differences in anuran defence behaviours. Issue 4 (4th July 2022) - Ferrante, Lucas; Najar, Thainá; Baccaro, Fabricio; Kaefer, Igor L.
Abstract : Anti-predator mechanisms play a key role in the survival of any animal in nature. Anurans exhibit a great diversity of defensive behaviours and interact with the widest range of predators of any vertebrates. However, there are few systematic and experimental studies of anuran defensive behaviours, which are generally opportunistic. Here, we deploy a range of methods to investigate various facets of anuran defensive behaviour using the cane toad Rhinella marina as a model organism. This originally Amazonian anuran is now widely distributed across the globe and has caused several predators to decline at introduction sites where this species is not native, a direct result of its anti-predation defenses. First, we compiled previously published data on anuran predation events to assess the relationship between predator/anuran size and predator size and type. We then performed a systematic experiment to test the hypothesis that there is an ontogenetic variation in cane toad behavioural defense displays, as well as a variation in these displays between males and females. In total, we tested 173 individuals including juveniles, adult males and adult females. We show that the size and type of the predator is related to the size of the anuran as prey and that this, in turn, has led to the adoption of different predation-avoiding behavioural defensive strategies during ontogeny. Our results also indicate that both the sex and the size of anurans influence the adoption of defensive strategies.